Preparation of aptamer‐bound polyamine affinity monolithic column via a facile triazine‐bridged strategy and application to on‐column specific discrimination of ochratoxin A. Issue 13 (3rd June 2019) - Yu, Xia; Lai, Shuoke; Wang, Li; Chen, Yiqiong; Lin, Xucong; Xie, Zenghong
Abstract: Developing a high‐performance modification protocol is critical for efficiently fabricating affinity monolith. Herein, by using 2, 4, 6‐trichloro‐1, 3, 5‐triazine as the linker, a simple triazine‐bridged approach was proposed for efficiently fabricating aptamer‐grafted polyhedral oligomeric silsesquioxane‐polyethyleneimine affinity monolith with high specificity toward ochratoxin A. Experimental parameters, column characteristics and specificity performances of the resultant affinity monolith were investigated in detail. Under the optimal conditions, 2, 4, 6‐trichloro‐1, 3, 5‐triazine was rapidly grafted on the polyamine matrix, and effectively applied to the subsequent bridge linkage of aptamers. It was simple and effective, which resulted in a significant decrease of modification time, excellent properties including the high coverage density of aptamer up to 1799 pmol/μL and sensitive detection of ochratoxin A as low as 10 pg/mL in beer samples. This protocol provides a facile approach for fabricating aptamer‐grafted polyamine affinity monoliths with highly selective discrimination performance.